Design and development of hexagonal-shaped copper and liquid metamaterial-loaded superstrate patch antenna for 5G, WLAN, tracking and detection applications - Meshari Alsharari; Raj Agravat; Sunil Lavadiya; Ammar Armghan; Khaled Aliqab; Shobhit K. Patel (Ain Shams Engineering Journal)
The novel T-shaped patch antenna with the superstrate approach is planned in the manuscript. The FR-4 dielectric material is used as a superstrate and substrate. The hexagonal-shaped rings are loaded in the superstrate to enable the metamaterial property in the structure. The copper-loaded metamaterial and liquid Sea water-loaded metamaterial are used in the planned antenna which increases the gain and BW of the planned antenna design. Different parametric analyses like the varying height of the superstrate and changing spacing among SRR rings are considered to achieve an optimum response. The analysis concerning S11, gain, and directivity is carried out among simple patch antenna, copper ring loaded structure and seawater loaded structure. The frequency span of 1 GHz to 12 GHz is considered for analysis. The planned designs provide a minimum S11 of −49.16 dB in CMRNGS, a Gain of 6.92 dB in SMRNGS, and a highest directivity of 8.56 dB for 8.83 GHz resonance. The planned design is compared with other papers to check the improvement of this planned antenna design. The Simulated and assessed responses were also compared and analysed. The planned design is suitable for 5G, WLAN, tracking and detection applications.